ANALISIS SEMIOTIKA ROLAND BARTHES PADA POSTER FILM HOROR THE MONKEY - Wildan, Wildan; Ryan Surya Saputra; Sri Wulandari (SNADES, 2025)
This study examines the film poster of The Monkey through Roland Barthes’ semiotic framework, focusing on the two levels of meaning: denotation and connotation. The poster presents an image of a monkey doll set in a dark atmosphere, bearing a disturbing expression, alongside provocative text and vivid colors. The analysis demonstrates that each visual component ranging from typography, color scheme, facial expression, and lighting to the background conveys not only a literal meaning but also constructs a psychological narrative centered on fear, hidden power, and emotional tension. These visual signs are effectively employed to evoke a sense of horror and influence the audience’s perception of the film’s themes. The findings underscore that film posters, as visual media, embody complex symbolic meanings that can be critically interpreted through semiotic analysis.